S83 The use of indwelling pleural catheters (IPC) with or without concurrent talc poudrage (TP) at medical thoracoscopy (MT) for cases of suspected trapped lung (TL). (14th November 2013) - Chatterji, S; Pulimood, T; Reid, E; Herre, J; Sivasothy, P
Abstract : Background: Recurrent symptomatic non-infectious pleural effusions can be effectively treated with MT and TP with pleurodesis rates approaching 85% in variety of malignant and benign aetiologies. When TL is likely at MT, management is uncertain. Aim: We report on a single centre experience of inserting an IPC at MT with or without talc poudrage for suspected trapped lung. TL was suspected if any of the following were observed (a) failure of lung to inflate on voluntary coughing at MT, (b) visceral involvement of more than 25%, (c) radiological evidence of endobronchial compromise and (d) hydropneumothorax following previous thoracocentesis. Method: A review of all IPC insertions at MT performed at our institution between March 2009 and Feb 2013 assessing indications, length of stay (LoS) after procedure, use of concurrent TP, IPC removal rates and recorded complications. All cases had been performed using rigid thoracoscopy. TP was performed with 4g sterile graded talc. Rocket 16F IPC were used in all cases. Results: All IPCs were inserted during MT for likely or possible TL. N = 36cases. 14 male. Diagnoses–10 benign recurrent effusions; 26 malignant. See table 1 for details. Median age 73yrs (45–92). Median LoS post procedure–non-elective 7 days (1–23); elective 2.5 days (0–6). 22 (56%) had concurrent TP (18 for malignancy). 14 (36%) had their IPC removed with median time to removal 40 days (28–119) and of these, 11 had received TP during MT. 20 patients have died during follow up (none procedure-related) of which 11 still had their IPC in situ . Complications–2 blocked drains (not talc group, 1 case needing additional thoracocentesis), 2 leaking caps (replaced). Discussion: IPC insertion at MT with or without TP for cases of suspected TL appears to be safe, effective and obviates the need for further pleural intervention at a later date. This potentially has significant benefits to the patient as well as a reduction in overall healthcare costs to the NHS. Using the above criteria predicted TL in 78% of patients. This single centre observation needs to be investigated by a larger multi-centre study in patients with suspected TL at MT.